2002
DOI: 10.1007/s11920-002-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Family, twin, and adoption studies of bipolar disease

Abstract: Bipolar disease features states of severe depression that usually fluctuate with at least one episode of intense elation or mania. It is a disorder that has been thought for some time to have a heritable component. The lifetime prevalence of bipolar disease in the general population is approximately 1%. In contrast, family studies have shown the approximate lifetime risk of a first-degree relative of a bipolar proband to be 5% to 10%. Moreover, studies of monozygotic twins show that their risk of contracting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 36 publications
2
40
0
2
Order By: Relevance
“…Adoption studies show that this familiality has a genetic basis, and twin studies demonstrate a high degree of heritability. 1 While a single gene might play a major role in some rare families, multiple genes and environmental factors are usually considered to underlie BPAD susceptibility in most families. Several chromosomal regions have been implicated by genetic linkage and association studies as potential sites of susceptibility loci, 2 but findings have proven difficult to replicate consistently.…”
mentioning
confidence: 99%
“…Adoption studies show that this familiality has a genetic basis, and twin studies demonstrate a high degree of heritability. 1 While a single gene might play a major role in some rare families, multiple genes and environmental factors are usually considered to underlie BPAD susceptibility in most families. Several chromosomal regions have been implicated by genetic linkage and association studies as potential sites of susceptibility loci, 2 but findings have proven difficult to replicate consistently.…”
mentioning
confidence: 99%
“…Family, twin, and adoption studies support a substantial genetic component for BP. 1 Linkage studies, including genome-wide scans, have implicated multiple chromosomal regions as possible sites for susceptibility loci. However, inconsistent results underscore the challenge in attaining compelling findings.…”
Section: Introductionmentioning
confidence: 99%
“…1 Family, twin and to a less extent adoption studies strongly support a genetic component of BPAD, buts its mode of inheritance remains unclear. [1][2][3] Genome-wide searches have detected numerous chromosomal regions possibly linked to BPAD, leading to conflicting results. A recent metaanalysis of 18 BPAD genome scan data sets 4 suggested that no chromosomal region achieved genome-wide statistical significance according to several simulation-based criteria.…”
Section: Introductionmentioning
confidence: 99%